(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The integration of technology has revolutionized various aspects of education, including the teaching and learning of English language skills. This article examines the diverse landscape of technological tools available for English language instruction and critically analyzes their potential benefits and limitations. Through a review of relevant research and pedagogical frameworks, we explore the impact of technology on various skill areas, including reading, writing, listening, speaking, and grammar. The article highlights the advantages of technology in promoting learner engagement, personalization, and access to authentic language experiences. However, it also addresses challenges such as digital divide issues, the need for effective teacher training, and the potential for overreliance on technology.